Insights into wheat grain microstructure and composition for the development of novel flour with slow digestion properties and enhanced functional characteristics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University, Palmerston North, New Zealand - Abhilasha (Massey University, 2025)
Wheat has been consumed as whole grains, broken grains, flattened format, and puffed format other than the flour format, which has a wide application in different types of food preparations. Wheat flour possesses a unique ability to form a cohesive dough that has viscoelastic properties. A range of products with wheat as their major ingredient are high glycaemic index (GI) foods as wheat flour contains highly digestible starch. However, the consumption of high GI foods is associated with chronic diseases such as diabetes, coronary heart disease, and obesity due to a rapid increase in blood glucose levels and secretion of insulin. The major objective of the research studies of this thesis included creating slowly digestible flour with improved functionality using slowly digested starch sources and non-starch components. Modifying wheat grain through different processing techniques alters the microstructure, and therefore, starch digestibility is impacted. Microstructure modification through various processing techniques, which can control the access of digestive enzymes to starch, could help develop products with controlled starch digestibility. To advance the understanding of the impact of wheat grain microstructure on starch hydrolysis, Chapter 3 explored a study on whole wheat grain in different commercially available forms (kibbled, cut grains, and flour) to understand the influence of microstructural changes on in vitro starch digestibility. The process of size reduction from raw intact grains to kibbled grains and flour caused an increase in overall starch hydrolysis (%) during simulated digestion in the order of flour>kibbled>cut>intact whole wheat grains. Cooking of these formats further increased their starch hydrolysis. However, both cooked cut and intact grains were low glycaemic with the expected glycaemic indices (eGI) of values of 54.08±0.03 and 41.98±0.04, respectively, revealing the role of intact microstructure in starch hydrolysis of wheat grains. Based on the role of intact microstructure, Chapter 4 investigated the possibility of reducing the starch hydrolysis in wheat grain formats (whole, flakes, and flour) by hydrothermal treatment and low-temperature storage of whole wheat grains. The extent of starch hydrolysis after oral-gastro-small intestinal digestion in vitro was significantly lower (p<0.05) in intact grains, flakes, and flours from the cold-stored grains than their non-cold-stored counterparts. In this study, scanning electron micrographs, pasting properties, water retention capacities, and relative crystallinity of the resulting flours revealed an enhanced degree of gelatinisation with the treatment temperature; however, cold-storage of treated grains resulted in a change in these properties due to the retrogradation of the starch. This study indicates that hydrothermal pre-treatment of grains followed by low-temperature storage for prolonged periods might help to reduce the starch digestibility of wheat grains and their resulting products and could be an effective strategy in developing reduced glycaemic impact grain products. However, in our preliminary trials, the flours from hydrothermally treated and low-temperature stored grains resulted in doughs of inferior viscoelastic properties. Furthermore, intending to create slowly digestible flour, Chapter 5 employed two approaches to modify a resistant starch: one involving soluble extracts from wheat flour and vital gluten (water solubles, salt-assisted water-solubles, and acid-solubles) and the other utilising hydrocolloids (guar gum, xanthan gum, locust bean gum, and carboxymethyl cellulose). Modifications from both approaches resulted in modified starch morphology with the formation of starch clusters mimicking the wheat flour. Moreover, the modification with hydrocolloids resulted in an improved pasting profile. Furthermore, in vitro digestion studies revealed that the starch hydrolysis rate was decreased for most of the cooked modified starches with wheat solubles and a slower starch hydrolysis profile until 60 min of simulated small intestinal digestion for most of the hydrocolloids used, carboxymethyl cellulose being the least effective in slowing the starch hydrolysis rate. Additionally, Chapter 6 evaluates the functionality and starch digestibility of a wheat flour system (dough and flatbread-chapatti) by utilising the modified starches created in Chapter 5 as low glycaemic ingredients. The interaction of the modified starches with vital gluten and wheat flour components resulted in improved viscosity of the functional flour. The microstructure of the functional flour dough indicated that the modified starches with wheat solubles (soluble extracts from wheat flour and vital gluten) and hydrocolloids improved the starch-protein matrix and gluten network. Furthermore, the in vitro digestion study revealed the overall starch hydrolysis of chapattis from all the functional flour formulations was significantly lower than the wheat flour chapatti. In conclusion, structural modifications of wheat grain could help reduce the overall starch hydrolysis of wheat grain products. Moreover, the wheat grain components have the potential to modify resistant starch sources to improve their functionality while retaining their slow digestion property. Also, utilising hydrocolloids to modify resistant starch sources could be an effective strategy to enhance the functionality of resistant starches in wheat-based systems. Modified resistant starches created using wheat solubles (soluble extracts from wheat flour and vital gluten) and hydrocolloids have potential applications with slow digestibility and improved functionality in wheat-based products.
Figures are reproduced with permission.
Keywords: wheat grain, wheat flour, whole grain, starch hydrolysis, in vitro starch hydrolysis, microstructure, resistant starch, modified resistant starch, dough, dough rheology; Wheat; Composition; Flour; Processing; Hydrolysis; Starch; 300607 Food technology